2013
DOI: 10.1016/s0140-6736(12)61566-9
|View full text |Cite
|
Sign up to set email alerts
|

Immunosuppression for progressive membranous nephropathy: a UK randomised controlled trial

Abstract: SummaryBackgroundMembranous nephropathy leads to end-stage renal disease in more than 20% of patients. Although immunosuppressive therapy benefits some patients, trial evidence for the subset of patients with declining renal function is not available. We aimed to assess whether immunosuppression preserves renal function in patients with idiopathic membranous nephropathy with declining renal function.MethodsThis randomised controlled trial was undertaken in 37 renal units across the UK. We recruited patients (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
114
0
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(124 citation statements)
references
References 21 publications
2
114
0
5
Order By: Relevance
“…At 3 years, the risk of further 20% decline in creatinine clearance was significantly lower in the prednisolone and chlorambucil group than in the supportive care group and this risk did not differ between the cyclosporine and supportive treatment-only groups. Serious adverse events were frequent in all three groups but were higher in the prednisolone and chlorambucil group than in the supportive care-only group (50). It is well known that cyclosporine may be contraindicated in nephrotic patients with serum creatinine .2.00 mg/dl (estimated creatinine clearance around 50 ml/min per 1.73 m 2 ), due to the possibility of nephrotoxicity.…”
Section: What Specific Treatments Are Available For Patients With Idimentioning
confidence: 81%
See 1 more Smart Citation
“…At 3 years, the risk of further 20% decline in creatinine clearance was significantly lower in the prednisolone and chlorambucil group than in the supportive care group and this risk did not differ between the cyclosporine and supportive treatment-only groups. Serious adverse events were frequent in all three groups but were higher in the prednisolone and chlorambucil group than in the supportive care-only group (50). It is well known that cyclosporine may be contraindicated in nephrotic patients with serum creatinine .2.00 mg/dl (estimated creatinine clearance around 50 ml/min per 1.73 m 2 ), due to the possibility of nephrotoxicity.…”
Section: What Specific Treatments Are Available For Patients With Idimentioning
confidence: 81%
“…The results of a randomized controlled trial that compared the effects of three different therapeutic approaches in adult patients with biopsy proven idiopathic MN and declining renal function were recently published (50). Criteria for inclusion included an initial serum creatinine level ,300 mmol/L (3.4 mg/dl) and at least a 20% decline in creatinine clearance measured in the 2 years before study entry.…”
Section: What Specific Treatments Are Available For Patients With Idimentioning
confidence: 99%
“…For a 55-year-old patient, this result translates into an increase in annual cancer risk from approximately 0.3% to 1.0% (13). Previous studies have shown that treatment with alkylating agents reduced the incidence of ESRD 3-to 5-fold (14)(15)(16)(17). At first glance, this decreased renal risk is matched by an increased risk of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest therapy and prognosis of MN are different in Japan and American or European countries. Recently, it was reported that 6 months' therapy with prednisolone and chlorambucil, but not with Cs A monotherapy, was effective for maintaining renal function in patients with IMN, and thus CsA monotherapy should be avoided in MN [6]. Nevertheless, in this study we administered our patient CsA as Irbesartan 100mg…”
Section: Discussionmentioning
confidence: 93%